2016
DOI: 10.1021/acs.jpcc.6b05707
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Vapor Adsorption on the Metal–Organic Framework NU-1000: Structure and Energetics

Abstract: The nature and energy of the reactions between calcium vapor and the internal surfaces of the metal–organic framework (MOF) NU-1000 have been studied by adsorption microcalorimetry, low energy He+ ion scattering spectroscopy (LEIS), X-ray photoelectron spectroscopy (XPS), and Kohn–Sham density functional theory (DFT). NU-1000 is one of the most stable MOFs with transition-metal-oxide nodes, and thus it is of interest as a potential catalyst or catalytic support when modified with other metals. The reaction hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 82 publications
0
26
0
Order By: Relevance
“…We had published a previous paper about the adsorption energy of calcium vapor onto this same type of NU-1000 sample synthesized by that same group, in which they were coauthors. 12 The Experimental Section of that joint paper with them says regarding defects: " 1 H NMR of the digested material confirmed that activation was complete, with the only carboncontaining component being the tetra-acid of the MOF organic linker, pyrene-tetraphenylcarboxylate. Nitrogen adsorption measurements of the activated MOF yielded the Brunauer− Emmett−Teller (BET) surface area, the pore volume, and the isotherm shape expected for a clean and undamaged sample.…”
Section: Methodsmentioning
confidence: 99%
“…We had published a previous paper about the adsorption energy of calcium vapor onto this same type of NU-1000 sample synthesized by that same group, in which they were coauthors. 12 The Experimental Section of that joint paper with them says regarding defects: " 1 H NMR of the digested material confirmed that activation was complete, with the only carboncontaining component being the tetra-acid of the MOF organic linker, pyrene-tetraphenylcarboxylate. Nitrogen adsorption measurements of the activated MOF yielded the Brunauer− Emmett−Teller (BET) surface area, the pore volume, and the isotherm shape expected for a clean and undamaged sample.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the bonding energetics of metal vapor adsorption onto NU-1000 for the metalation of the nodes has been investigated using different experimental techniques and density functional theory (DFT). 139 The other common method for cluster metalation in a pyrene-based MOF is solvothermal deposition in MOF (SIM), which is complementary to gas-phase metalation of the node (AIM). In this method, the modifying metal species are dissolved in a non-reactive solvent (e.g.…”
Section: Post-synthetic Modification Of Pyrene-based Mofsmentioning
confidence: 99%
“… 95 , 96 The M06-L functional has been validated for many applications relevant to catalysis 97 119 (including some cases very similar to the cases discussed in the next section but also including studies relevant to the broader applicability for transition metal catalysis and barrier heights) and MOFs. 120 , 121 …”
Section: Computational Methods and Modelsmentioning
confidence: 99%
“…Among the density functionals that have proven useful in the KS-DFT context, we single out the Minnesota functional M06-L, , which has shown a good performance in reproducing experimental trends and being able to accurately predict spin-state energetics in MOFs in good agreement with high-level methods, such as the CASPT2 method. , The M06-L functional has been validated for many applications relevant to catalysis (including some cases very similar to the cases discussed in the next section but also including studies relevant to the broader applicability for transition metal catalysis and barrier heights) and MOFs. , …”
Section: Computational Methods and Modelsmentioning
confidence: 99%
See 1 more Smart Citation